Surgery of Larynx and Trachea - Remacle, Marc.; Eckel, Hans Edmund; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
I have been honoured to write the foreword to this European Textbook on Surgery of Larynx and Trachea. This multi-author textbook under the editorship of Professor Marc Remacle and Professor Hans Eckel is de? nitely a milestone in European laryngology and for the European Laryngological Society. The editors and the chapter authors belong to the leading laryngologists in Europe. The book covers a broad ? eld within larynx and trachea and represents the state of art within European laryngology today. The book covers physiology, phoniatrics, open, and endoscopic operative techniques in adults and in pediatrics. Even assisting drugs used in clinical practice as steroids, ? brin glue, mitomycin C, cidofovir, etc. have been covered. The book is easy to read, but goes into depths of representative ? elds. On the whole, the book is very well illustrated, not only with endoscopic photos, but also with a lot of illustrative drawings which complement and add to the quality of the chapters. I am sure that this is a book that will be read, not only by laryngologists in Europe and outside, but also used in the teaching of residents and those superspecializing in laryngology. As one of the founding members of ELS and President of EUFOS, I must congra- late all the authors and editors of this European Textbook on Larynx and Trachea. The book is an example of the standard and quality of European ORL-HNS and especially laryngology today. The book is de? nitely very promising for the future.
Physiology of Voice Production -- Assessment of Voice and Respiratory Function -- Fundamentals of Laryngeal Surgery: Approaches, Instrumentation, and Basic Microlaryngoscopic Techniques -- Endolaryngeal Phonosurgery -- Microphonosurgery Using Cold Instruments -- Laser-Assisted Microphonosurgery -- Laryngeal Framework Surgery -- Laryngeal Surgery in Children -- Surgery for Benign Tumors of the Adult Larynx -- Laryngotracheal Blunt Trauma -- Glottic Airway Stenosis -- Subglottic and Tracheal Stenosis -- Tracheotomy -- Scarred Larynx -- Synechia of the Anterior Commissure -- Treatment Options for Laryngeal and Hypopharyngeal Cancer -- Endoscopic Approach -- Open Partial Resection for Malignant Glottic Tumors -- Surgery for Laryngeal and Hypopharyngeal Cancer -- Total Laryngectomy -- Voice Restoration -- Neurolaryngology -- Swallowing Disorders -- Nerve Reconstruction -- Helping Drugs -- Preoperative and Postoperative Speech Therapy.
Keywords: Medicine; Otorhinolaryngology; Otolaryngologic surgery; Surgery; Minimally invasive surgery; Plastic surgery; Medicine & Public Health; Otorhinolaryngology; Plastic Surgery; Head and Neck Surgery; Surgery; Minimally Invasive Surgery; Electronic books